Genetic diversity of norovirus in Shenzhen Based on continuous surveillance from 2016 to 2022 - Wang, Xin; Liu, Wanqiu; Hu, Mingda; Ma, Hui; He, Yaqing; Wang, Boqian; Li, Kexin; Zhang, Rui; Fu, JingJing; Zhang, Hailong; Chen, Long; Zhao, Xinru; et al. (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionNorovirus is a key pathogen of acute gastroenteritis and poses a significant burden on both the economy and public health. This study focuses on continuous monitoring of norovirus in Shenzhen, China, from 2016 to 2022, aiming to analyze the epidemic characteristics and genetic diversity of norovirus in the context of global sequence data.MethodsThe study was based on data collected from local sentinel hospitals. It involved analyzing the demographic, spatial, and temporal distribution of norovirus infections. Phylogenetic analysis was conducted, and genotype dynamics were compared across geographic levels. Mutations affecting protein stability were evaluated, and recombination analysis was performed to identify critical breakpoints and fragments for norovirus.ResultsThe study found that norovirus primarily infected infants under 3 years old, with epidemics occurring in winter and concentrated in developed districts. Phylogenetic analysis revealed both similarities and differences in the evolutionary patterns of various genotypes at different geographical levels. Mutations in the VP1 protein, based on the protein structure of GII.4_Sydney[P31], provided insights into the evolutionary trends of key genotypes. Additionally, recombination analysis identified important breakpoints and fragments for norovirus.DiscussionThe findings offer valuable insights to evolution and transmission of norovirus. These results can serve as a reference for future research, and they may aid in vaccine development efforts aimed at controlling norovirus outbreaks.